Pengaruh Fanatisme Budaya Dan Minat Beli Terhadap Keputusan Pembelian Pada Produk Makanan Gabus Pucung Di Bekasi - Nicky Liane Yonatan; Dhian Tyas Untari; Istianingsih Istianingsih; Chris Kuntadi (Jurnal Kajian Ilmiah, 2024)
Betawi Ora culture is an indigenous culture of the people in Bekasi. According to research conducted by previous researchers, it states that the existence of Betawi Ora culinary culture is experiencing degradation. So that research related to Betawi Ora culinary culture is important to be explored as a reference in maintaining the existence and sustainability of Betawi Ora culture in Bekasi. One of the culinary icons of Betawi Ora is Gabus Pucung, which ecologically the culinary ingredients are still widely available in Bekasi. This study has 2 objectives, namely teleological objectives and operational objectives. The teleological objective of this study is one of the efforts of researchers who have concerns and focus on Betawi Culinary Culture to obtain a stepping stone in the strategy of developing culinary culture through aspects of market demand. While from the aspect of operational objectives; researchers want to see the influence of Betawi cultural fanaticism on the decision to purchase Gabus Pucung culinary and purchase interest as an intervening variable. The study involved 96 samples with the accidental sampling technique. The respondent criteria are those or consumers who have been and are existing consumers of Gabus Pucung culinary in Bekasi. This study uses multivariate statistical analysis techniques using SPSS.